Global Food Security and Wellness - Barbosa-Cánovas, Gustavo V.; María Pastore, Gláucia; Candoğan, Kezban; Medina Meza, Ilce G.; Caetano da Silva Lannes, Suzana; Buckle, Ken; Yada, Rickey Y.; Rosenthal, Amauri (Springer New York : Imprint: Springer, 2017)
This book is based on selected papers from keynote and symposium sessions given at the 16th International Union of Food Science and Technology (IUFoST) World Congress, held in Foz do Iguaçu, Brazil, in August, 2012. The theme of the Congress was the challenges faced by food science in both the developed and developing regions of the world. The symposia featured prominent, world-renowned keynote and plenary speakers and young researchers, and the technical sessions covered the whole spectrum of basic and applied food science and technology, including consumer issues and education, diets and health, ethnic foods and R&D.